Hair as a Biomarker of Environmental Manganese Exposure - Eastman, Rachel R. (2013)
The absence of well-validated biomarkers of manganese (Mn) exposure in children remains a major obstacle for studies of Mn toxicity. We developed a hair cleaning methodology to establish the utility of hair as an exposure biomarker for Mn and other metals (Pb, Cr, Cu), using ICP-MS, scanning electron microscopy, and laser ablation ICP-MS to evaluate cleaning efficacy. Exogenous metal contamination on hair that was untreated or intentionally contaminated with dust or Mn-contaminated water was effectively removed using a cleaning method of 0.5% Triton X-100 sonication plus 1N nitric acid sonication. This cleaning method was then used on hair samples from children (n=121) in an ongoing study of environmental Mn exposure and related health effects. Mean hair Mn levels were 0.121 μg/g (median = 0.073 μg/g, range = 0.011 – 0.736 μg/g), which are ~4 to 70-fold lower than levels reported in other pediatric Mn studies. Hair Mn levels were also significantly higher in children living in the vicinity of active, but not historic, ferroalloy plant emissions compared to controls (P<0.001). These data show that exogenous metal contamination on hair can be effectively cleaned of exogenous metal contamination, and they substantiate the use of hair Mn levels as a biomarker of environmental Mn exposure in children.